Epizootic shell disease induces systemic transcriptomic shifts in Homarus americanus, characterized by increased shell degradation and impaired energy metabolism across tissues - Kim, Minseo; Cao, Dianjun; Cavaleri, Vincent; Han, Kyudong; Mun, Seyoung; Jeon, Soo Jin (Frontiers in Physiology, 2025)
Epizootic shell disease (ESD) is characterized by shell erosion, pitting, and melanization in the American lobster (Homarus americanus) and is associated with a polymicrobial infection. The disease is multifactorial, with several contributing factors such as rising water temperatures and environmental pollution, which may facilitate bacterial invasion and increase host susceptibility. In a previous study, we found that the microbiome composition of the carapace in lobsters with ESD differed from that of healthy individuals, with ESD-associated bacteria enriched in the green gland and testis. However, the effects of bacterial infection on internal organs have not been clearly identified. In this study, we investigated the effects of ESD on four major tissues of the lobster (testis, intestine, hepatopancreas, and green gland) using transcriptomic analysis. A total of 564 genes were differentially expressed in the testis, 105 in the intestine, 333 in the hepatopancreas, and 112 in the green gland. The expression of the anti-lipopolysaccharide factor gene was increased in all tissues, indicating a systemic immune response to bacterial infection. Notably, chitinase genes involved in chitin degradation were upregulated, while the acetyl-coenzyme A transporter 1-like gene related to energy metabolism was significantly downregulated in the testis. In the intestine, expression of phosphoenolpyruvate carboxykinase cytosolic [GTP] and cytochrome P450 genes, which are involved in gluconeogenesis and xenobiotic metabolism, respectively, was reduced. The hepatopancreas showed decreased expression of hemocyanin genes, which play key roles in oxygen transport and immune defense in crustaceans. The green gland exhibited reduced expression of heat shock proteins involved in the cellular stress response, organic cation transporter proteins that mediate the excretion of organic cations, and UDP-xylose and UDP-N-acetylglucosamine transporters required for glycosylation and chitin biosynthesis. Together, these transcriptional changes suggest that ESD may compromise physiological functions such as immune defense, energy metabolism, and stress response, while promoting chitin degradation and cuticle remodeling in response to shell infection. This study revealed tissue-specific transcriptomic responses to ESD in the American lobster, providing a foundation for elucidating the molecular mechanisms underlying disease progression.